The Presence of Serum TgAb Suggests Lower Risks for Glucose and Lipid Metabolic Disorders in Euthyroid General Population From a National Survey - Jinjia Zhang (Frontiers in Endocrinology, 2020)
Purpose: The expressions of antibodies against thyroid peroxidase (TPOAb) and thyroglobulin (TgAb) are very common in the sera of patients with autoimmune thyroid diseases (AITD). The relationship between thyroid autoantibodies and the occurrence of glucose and lipid metabolic disorders remains unclear. This study was performed to investigate the correlation between the presence of serum TPOAb/TgAb and those metabolic disorders in euthyroid general population.Methods: The data of this study were derived from the Thyroid Disease, Iodine status, and Diabetes National epidemiological (TIDE) survey from all 31 provinces of mainland China. A total of 17,964 euthyroid subjects including 5,802 males (4,000 with TPOAb−TgAb− and 1,802 with TPOAb+/TgAb+) and 12,162 females (8,000 with TPOAb−TgAb− and 4,162 with TPOAb+/TgAb+) were enrolled in this study. The blood glucose and lipid levels were compared between individuals with TPOAb−TgAb− and those with TPOAb+TgAb−, TPOAb−TgAb+, TPOAb+TgAb+.Results: Both fasting blood glucose (FBG) concentration and the proportion of individuals with impaired FBG (IFG) showed the decreased trends in TPOAb−TgAb+ males as compared with TPOAb−TgAb− men. There were significantly lower FBG and higher HDL-C levels as well as tendencies toward decreased incidences of IGT and hypertriglyceridemia in TPOAb−TgAb+ females when compared with TPOAb−TgAb− women. Binary logistic regression analysis further showed that serum TgAb single positivity in males was an independent protective factor for IFG with an OR of 0.691 (95% CI, 0.503–0.949). For females, serum TgAb single positivity was an independent protective factor for hypertriglyceridemia with an OR of 0.859 (95% CI, 0.748–0.987). Trend test showed that with the increase of serum TgAb level, there were significant decreases in the prevalence of IFG among the men with TSH ≤ 2.5 mIU/L and that of hypertriglyceridemia in the women, especially among non-obese females.Conclusion: Serum TgAb single positivity may imply a reduced risk of IFG in euthyroid men and that of hypertriglyceridemia in euthyroid women. The mechanisms for the independent protective roles of TgAb await further investigation.